Molecular and Pathogenic Diversity Among Brazilian Isolates of Xanthomonas albilineans Assessed with SSR Marker Loci - Tardiani, Ana C. [UNESP]; Perecin, Dilermando [UNESP]; Peixoto-Junior, Rafael F.; Sanguino, Alvaro; Landell, Marcos M. G.; Beriam, Luis O.; Nunes, Daniel S.; Camargo, Luis E. A.; Creste, Silvana (Amer Phytopathological Soc, 2014)
Leaf scald is one of the most important diseases of sugarcane in Brazil. Despite its importance, little is known about the genetic and pathogenic variability of its causal agent, Xanthomonas albilineans. The genetic diversity of 44 X. albilineans isolates from diverse geographic regions of Brazil was assessed using 15 newly developed short sequence repeat (SSR) loci designed from the genome sequence of X. albilineans strain GPE PC73. In addition, the aggressiveness of each isolate was evaluated by inoculating on a susceptible sugarcane cultivar and scoring the disease severity. Of the 15 SSR loci, 12 were polymorphic and produced 54 polymorphic alleles. The average number of polymorphic alleles per locus was 4.5, and ranged from 2 to 12 alleles. Phenetic analysis based on Nei's unbiased genetic distance, clustered the isolates into two major groups. Group I included 32 isolates from all four geographic regions studied, whereas group II included 9 isolates from two regions. Three isolates did not cluster within these groups. Analysis of disease severity data also revealed variability in aggressiveness among isolates but no correlation could be established with either SSR haplotypes or phenetic groups. Isolates with identical haplotypes differed in aggressiveness and vice versa. However, single marker-trait analysis revealed two markers associated with this trait.